2008
DOI: 10.2223/jped.1772
|View full text |Cite
|
Sign up to set email alerts
|

Furazolidone, tetracycline and omeprazole: a low-cost alternative for <i>Helicobacter pylori</i> eradication in children

Abstract: ResumoObjetivos: Avaliar furazolidona, tetraciclina e omeprazol como tratamento de primeira linha para Helicobacter pylori em crianças com sintomas digestivos.Métodos: Ensaio clínico aberto, prospectivo e consecutivo. O estudo incluiu pacientes acima de 8 anos com dispepsia funcional, dor abdominal funcional, anormalidades histológicas graves (metaplasia intestinal, atrofia gástrica ou linfoma do tecido linfóide associado às mucosas) ou úlcera péptica. A presença de H. pylori foi definida com base em exame his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…In Brazil other studies were done with the same antibiotics. Our study presented a side effects rate of 49%, compatible with the scientific literature, which advocates between 34-59.7% [9,10]. In Silva et al [10] the rate of reported side effects for the same therapeutic scheme was 34% 10, while in Machado et al [9] it was 47.2%.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In Brazil other studies were done with the same antibiotics. Our study presented a side effects rate of 49%, compatible with the scientific literature, which advocates between 34-59.7% [9,10]. In Silva et al [10] the rate of reported side effects for the same therapeutic scheme was 34% 10, while in Machado et al [9] it was 47.2%.…”
Section: Resultssupporting
confidence: 89%
“…The low complexity of the therapeutic scheme favors patients adherence to the treatment and, consequently, success which can be seen in the high eradication rates obtained (96%). Furthermore, this therapeutic scheme had its efficacy proved by two other studies: Silva et al found an intention-to-treat efficacy of 69% and in Machado et al [9] H. pylori eradication rates were 83.3% patients in intentionto-treat analysis and 89.7% in per-protocol analysis [9,10].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The treatment is performed for 7 days, the doses of furazolidone used range from 100 mg (children) to 400 mg/day, with frequent adverse effects, particularly gastrointestinal (28,35,63,107,128) . A systematic review and meta-analysis of the effects of furazolidone and nitrofurantoinic derivatives in eradicating H pylori showed that schemes using such drugs had more frequent adverse effects and slightly less effective eradication rates when compared with the classic triple therapy (12) .…”
Section: Statement 29mentioning
confidence: 99%